(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Computed tomography is one of the medical imaging tests in diagnosis. Multiple images of the inside of the body get captured in CT, like in traditional x-ray, but in various planes, can reformat the generated images. In CT, more excellent images are captured than in x-rays, especially for soft tissue and blood vessels. Four pairs of sinuses are there in the body, and small openings connect each to the nasal cavity. Out of the four sinuses, the paranasal sinus, a hollow and air-filled space, is located within the bones of the face. A vital role is played by Computed Tomography (CT) in the study of Paranasal Sinuses to diagnose and determine the various diseases related to paranasal sinuses. For example, multiple conditions like inflammatory, malignant neoplastic, and benign affect the paranasal sinus; all these conditions are diagnosed by CT Scans which directly help reduce the mortality and morbidity in patients suffering from diseases that affect the paranasal sinus. Besides this, CT Scans of paranasal sinus before functional endoscopic sinus surgery also help evaluate paranasal sinus disease and many more. The article aims to study the pathologies for which paranasal sinuses are affected and CT features of paranasal sinus diseases. Paranasal sinus computed tomography scans are performed for the measurements of – the volume of the nasal cavity. CT scan is also essential in evaluating anatomical variations to prove the correlation between the extent of disease and disease process in Sinonasal polyposis patients. Also, because of CT, paranasal sinus anatomy is delineated. This is the overview of the role of CT in paranasal sinus study (diagnostic, anatomical).